Syncope due to non-sustained episodes of Torsade de Pointes associated to androgen-deprivation therapy use: a case presentation (2021)
Background Abiraterone is a medication frequently used for metastatic castrate-resistant prostate cancer. We report a case of non-sustained episodes of TdP associated with severe hypokalemia due to androgen-deprivation therapy. Few case presentations describe this association; the novelty lies in the potentially lethal cardiovascular events among cancer patients receiving hormonal therapy. Case presentation A 70-year-old male presented with recurrent syncope without prodrome. ECG revealed frequent ventricular ectopy, non-sustained episodes of TdP, and severe hypomagnesemia and hypokalemia. During potassium and magnesium infusion for repletion, the patient underwent temporary transvenous atrial pacing. As part of the work-up, coronary angiography revealed a mild coronary artery disease, and transthoracic echocardiogram showed a moderately depressed ejection fraction. After electrolyte disturbances were corrected, the QT interval normalized, and transvenous pacing was no longer necessary. Abiraterone was discontinued during the admission, and the patient returned to baseline. Conclusions Cancer treatment is complex and requires a multidisciplinary approach. We presented a case of non-sustained TdP associated with androgen-deprivation therapy in an elderly patient with mild coronary artery disease and moderately reduced ejection fraction. Close follow-up and increased awareness are required in patients with hormonal treatment, especially in the setting of other cardiovascular risk factors.